PENGARUH GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BEI TAHUN 2022 – 2024 - Josephine Elliska Dinata; Sri Rahayuningsih (Jurnal Akuntansi dan Bisnis, 2026)
This research seeks to determine whether differences in profitability and the quality of Good Corporate Governance shape the extent to which Corporate Social Responsibility is carried out. The findings are intended to provide benefits for enterprises and stakeholders in strengthening the quality of corporate governance and CSR activities in the healthcare industry, as well as in sustaining profitability stability and growth effectively. The study population comprises IDX-listed healthcare companies for 2022–2024. From this population, eight healthcare firms meeting the established inclusion criteria were chosen as the research sample. The study adopted a quantitative design and tested the proposed relationships using multiple linear regression in SPSS version 29. The results demonstrate that Corporate Social Responsibility is significantly driven by Good Corporate Governance, is positively and significantly associated with profitability, and is significantly explained by the combined influence of profitability and Good Corporate Governance